Synthesis, reaction and structural studies of triorganotin carboxylates / Thong Pui Yee - Thong Pui, Yee (2012)
iiiC6H4CH(Br)CH(OCH3)COOH was obtained as the major product. The triorganotin diorganodithiocarbamylacetate were found to be inert towards any brominating agents. The bromination products were characterized by spectroscopic techniques such as 1H, 13C NMR and FT-IR spectroscopies. The X-ray structures of four bromination products namely 2,3-dibromo-3-phenylpropionic acid (A6), 2-bromo-3-methoxy-3-(p-methoxyphenyl)propionic acid (A7), bis(4,4-dimethyl-aminopyridinium)-2,3-dibromo-3-(p-chlorophenyl)propionate (A9) and tricyclohexyltin 2,3-dibromo-3-phenylprionate (P4) were also determined.In addition, ten selected triorganotin carboxylates, C4–C10, C14, P4–P6 were investigated for their cytotoxic activities against the human leukemia HL60 cells. In general, the triorganotin carboxylates exhibit comparable cytotoxic activities to that of cisplatin.